Pelatihan Pembuatan Pupuk Hayati, Agens Hayati dan Pestisida Nabati Desa Aunupe Kabupaten Konawe Selatan - La Ode Santiaji Bande; Andi Khaeruni R; Saefuddin; Aceng Haetami; Laode Alwi; Mariadi; Vit Neru Satrah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
The implementation of sustainable organic farming is an effort to address the problem of the use of inorganic fertilizers and synthetic pesticides which are increasingly used by farmers because their use has a negative impact. The target of implementing community service activities integrated with the Thematic Community Service Program is farmers in Aunupe Village, Wolasi District, Konawe Selatan District, which have been designated as Organic Farming Areas. Farmers in Aunupe Village mostly still use inorganic fertilizers and synthetic pesticides. The purpose of this activity is to provide farmers with an understanding of organic farming through training in the manufacture of biological fertilizers, biological agents and plant-based pesticides. The output from this activity is expected to gradually reduce farmers no longer use inorganic fertilizers and synthetic pesticides and begin to shift to the application of organic questions.